Dietary sodium induces a redistribution of the tubular metabolic workload. (15th October 2017) - Udwan, Khalil; Abed, Ahmed; Roth, Isabelle; Dizin, Eva; Maillard, Marc; Bettoni, Carla; Loffing, Johannes; Wagner, Carsten A.; Edwards, Aurélie; Feraille, Eric
Abstract : Key points: Body Na + content is tightly controlled by regulated urinary Na + excretion. The intrarenal mechanisms mediating adaptation to variations in dietary Na + intake are incompletely characterized. We confirmed and expanded observations in mice that variations in dietary Na + intake do not alter the glomerular filtration rate but alter the total and cell‐surface expression of major Na + transporters all along the kidney tubule. Low dietary Na + intake increased Na + reabsorption in the proximal tubule and decreased it in more distal kidney tubule segments. High dietary Na + intake decreased Na + reabsorption in the proximal tubule and increased it in distal segments with lower energetic efficiency. The abundance of apical transporters and Na + delivery are the main determinants of Na + reabsorption along the kidney tubule. Tubular O2 consumption and the efficiency of sodium reabsorption are dependent on sodium diet. Abstract: Na + excretion by the kidney varies according to dietary Na + intake. We undertook a systematic study of the effects of dietary salt intake on glomerular filtration rate (GFR) and tubular Na + reabsorption. We examined the renal adaptive response in mice subjected to 7 days of a low sodium diet (LSD) containing 0.01% Na +, a normal sodium diet (NSD) containing 0.18% Na + and a moderately high sodium diet (HSD) containing 1.25% Na + . As expected, LSD did not alter measured GFR and increased the abundance of total and cell‐surface NHE3, NKCC2, NCC, α‐ENaC and cleaved γ‐ENaC compared to NSD. Mathematical modelling predicted that tubular Na + reabsorption increased in the proximal tubule but decreased in the distal nephron because of diminished Na + delivery. This prediction was confirmed by the natriuretic response to diuretics targeting the thick ascending limb, the distal convoluted tubule or the collecting system. On the other hand, HSD did not alter measured GFR but decreased the abundance of the aforementioned transporters compared to NSD. Mathematical modelling predicted that tubular Na + reabsorption decreased in the proximal tubule but increased in distal segments with lower transport efficiency with respect to O2 consumption. This prediction was confirmed by the natriuretic response to diuretics. The activity of the metabolic sensor adenosine monophosphate‐activated protein kinase (AMPK) was related to the changes in tubular Na + reabsorption. Our data show that fractional Na + reabsorption is distributed differently according to dietary Na + intake and induces changes in tubular O2 consumption and sodium transport efficiency. Key points: Body Na + content is tightly controlled by regulated urinary Na + excretion. The intrarenal mechanisms mediating adaptation to variations in dietary Na + intake are incompletely characterized. We confirmed and expanded observations in mice that variations in dietary Na + intake do not alter the glomerular filtration rate but alter the total and cell‐surface expression of major Na + transporters all along the kidney tubule. Low dietary Na + intake increased Na + reabsorption in the proximal tubule and decreased it in more distal kidney tubule segments. High dietary Na + intake decreased Na + reabsorption in the proximal tubule and increased it in distal segments with lower energetic efficiency. The abundance of apical transporters and Na + delivery are the main determinants of Na + reabsorption along the kidney tubule. Tubular O2 consumption and the efficiency of sodium reabsorption are dependent on sodium diet.